Pengaruh Direct Compensation dan Indirect Compensation terhadap Motivation Karyawan Hotel Selabintana Sukabumi - Herni Herdiani; Seni Safitri (Institut Manajemen Wiyata Indonesia & Asosiasi Peneliti Manajemen Indonesia, 2019)
The purpose of this study is to examine the effect of direct and indirect compensation towards the employee's motivation at Selabintana Hotel & Conference Resort Sukabumi simultaneously and partially. The method of this research is quantitative method by using questionnaires. The samples of this study are 102 respondents. Descriptive analysis techniques are used on this research, with validity test, reliability test, classic assumption test, and multiple linear analysis. And then, the hypotheses tests are using F test and t test. The simultaneous test result is the direct and indirect compensation has significantly influence towards employee’s motivation. And the partial test showed that the direct compensation has a significant effect on employee’s motivation. And also the indirect compensation affect significantly the employee's motivation too.